Loss of Sarcomeric Scaffolding as a Common Baseline Histopathologic Lesion in Titin-Related Myopathies. Issue 12 (25th October 2018) - Ávila-Polo, Rainiero; Malfatti, Edoardo; Lornage, Xavière; Cheraud, Chrystel; Nelson, Isabelle; Nectoux, Juliette; Böhm, Johann; Schneider, Raphaël; Hedberg-Oldfors, Carola; Eymard, Bruno; Monges, Soledad; Lubieniecki, Fabiana; et al.
Abstract: Titin-related myopathies are heterogeneous clinical conditions associated with mutations in TTN . To define their histopathologic boundaries and try to overcome the difficulty in assessing the pathogenic role of TTN variants, we performed a thorough morphological skeletal muscle analysis including light and electron microscopy in 23 patients with different clinical phenotypes presenting pathogenic autosomal dominant or autosomal recessive (AR) mutations located in different TTN domains. We identified a consistent pattern characterized by diverse defects in oxidative staining with prominent nuclear internalization in congenital phenotypes (AR-CM) (n = 10), ± necrotic/regenerative fibers, associated with endomysial fibrosis and rimmed vacuoles (RVs) in AR early-onset Emery-Dreifuss-like (AR-ED) (n = 4) and AR adult-onset distal myopathies (n = 4), and cytoplasmic bodies (CBs) as predominant finding in hereditary myopathy with early respiratory failure (HMERF) patients (n = 5). Ultrastructurally, the most significant abnormalities, particularly in AR-CM, were multiple narrow core lesions and/or clear small areas of disorganizations affecting one or a few sarcomeres with M-band and sometimes A-band disruption and loss of thick filaments. CBs were noted in some AR-CM and associated with RVs in HMERF and some AR-ED cases. As a whole, we described recognizable histopathological patterns and structural alterations that could point toward considering the pathogenicity of TTN mutations.